THE CASH MANAGEMENT STRATEGY OF SYARIAH PROPERTY COMPANIES TO MAINTAIN BUSINESS CONTINUITY - Yeni Putri Lintang Sari; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
The purpose of this study is to find out cash management carried out by sharia property companies. This study uses a qualitative approach with descriptive case study strategy. The data in this study were obtained through primary data in the form of interviews and secondary data in the form of documentation based on two informants from PT Emirate Nusantara and PT Indo Tata Graha, respectively. The results of this study indicate that PT Emirate Nusantara and PT Indo Tata Graha manage cash by arranging sales schemes and payment schemes to maintain cash availability, and the two companies diversify their business as an effort to maintain business continuity.Keywords: Cash management, Sharia Property, business continuityREFFERENCE Al-Quran dan Terjemahannya. (2016). Jakarta: Kementerian Agama RepublikAssauri, Sofjan. (2007). Manajemen Pemasaran. Jakarta: Rajawali Pers.Brigham, Eugene F. dan Joel F. Houston. (2011). Dasar-dasar Manajemen Keuangan, Edisi Kesebelas. Buku 2. Jakarta: Salemba Empat.Djarwanto Ps. (2001). Pokok–pokok Analisa Laporan Keuangan. Edisi Pertama. Cetakan Kedelapan. Yogyakarta: BPFE. Firmansyah, E. A. (2016). Non-Bank approach in Islamic mortgage: The evidence from Indonesia. In The 4th WAIBS Conference, 1-7.Firmansyah, E. A., & Gunardi, A. (2018). A new paradigm in Islamic housing: Non-bank Islamic mortgage. Al-Iqtishad Journal of Islamic Economics, 10(2), 313-324.Handayani, N. (2007). Modal sosial dan keberlangsungan usaha (studi deskriptif kualitatif tentang keterkaitan hubungan modal sosial dengan keberlangsungan usaha pengusaha batik di kampung kauman, kelurahan kauman, kecamatan pasar kliwon, Surakarta. Disertasi tidak diterbitkan. Surakarta: Universitas Sebelas Maret.Moelong, Lexy J. (2009). Metode penelitian kualitatif. Bandung: PT Remaja Rosdakarya.Munawir. (2000). Analisa laporan keuangan. Yogyakarta: Liberty.Prawironegoro, Darsono. (2006). Manajemen keuangan. Jakarta: Diadit Media.Rizal, Yahya dkk. (2009). Akuntansi perbankan syariah. Jakarta: PT. Salemba Empat.Sugiyono. (2009). Metode penelitian bisnis (pendekatan kuantitatif, kualitatif, dan R&D). Bandung: CV Alfabeta.Sutrisno. (2007). Manajemen keuangan teori, konsep, dan aplikasi. Yogyakarta: EKONISIA. Tjiptono, Fandy. (2008). Strategi pemasaran. Edisi 3. Yogyakarta: Andi. Yin, Rober K. (2010). Studi kasus design & metode. Jakarta: Raja Grafindo Persada.